2017
DOI: 10.3233/jad-170105
|View full text |Cite
|
Sign up to set email alerts
|

Situation Model for Situation-Aware Assistance of Dementia Patients in Outdoor Mobility

Abstract: Background:Dementia impairs spatial orientation and route planning, thus often affecting the patient’s ability to move outdoors and maintain social activities. Situation-aware deliberative assistive technology devices (ATD) can substitute impaired cognitive function in order to maintain one’s level of social activity. To build such a system, one needs domain knowledge about the patient’s situation and needs. We call this collection of knowledge situation model.Objective:To construct a situation model for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
19
0
2
Order By: Relevance
“…We have also followed the approach when annotating the behaviour of people with dementia during their outdoor mobility [ 50 ]. People with dementia do act goal-oriented.…”
Section: Discussionmentioning
confidence: 99%
“…We have also followed the approach when annotating the behaviour of people with dementia during their outdoor mobility [ 50 ]. People with dementia do act goal-oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Wearable sensor data and data provided by the GRAIL system are synchronized by an event-based mechanism (ie, participants perform a distinctive movement at the beginning of the recording, which can be easily located in all sensors) and are resampled to 100 Hz. All wearable sensors have been used in previous studies [ 6 , 30 ] and validated [ 31 - 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…An offline annotation procedure was applied to the video data recorded during the orientation task, for assessing the observable orientation behavior of the participants using the ELAN 5.8 tool (The Language Archive) [ 36 ]. As a coding scheme, we used an adequate adaption of the coding scheme provided by Yordanova et al [ 30 ]. The same scheme has been used in the SiNDeM field study [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The importance of this distinction becomes obvious when applied to situation-aware assistive systems (e.g., Krüger et al, 2014;Yordanova et al, 2017). Translating the authors' suggested theoretical extension to include situational information by applying machine-readable data interpretation systems (ontologies), these groups have succeeded, for instance, in detecting, with great precision, situational instances of reallife disorientation in older persons.…”
Section: Lawton Revisitedmentioning
confidence: 99%